Beyond the Mosque: Social Media as A New Frontier for Islamic Moral Education - Nasution, Suryadi; Nur, Kholidah; Khairurrijal, Khairurrijal; Pohan, Ali Jusri (Al Ulya: Jurnal Pendidikan Islam, 2025)
This study aims to investigate the potential of social media as an instrument for Islamic moral education in Indonesia, a context with 167 million internet users and 77% internet penetration in 2023, to transcend the traditional role of mosques. Employing a qualitative methodology through a multiple case study design, data were collected via semi-structured interviews with 30 informants aged 15–35 years in North Sumatra, selected through purposive sampling, alongside content analysis of 150 posts on Instagram, TikTok, and YouTube, validated using source triangulation. The findings reveal that digital formats such as short videos (averaging 50,000 views), infographics (32,000 views), and Islamic challenges (#challengeislami, 450 posts) are effective in internalizing moral values, supported by interactivity and wide reach. However, religious hoaxes (12% of the sample) and secular distractions pose challenges to the sustainability of impact. The study proposes a model based on the synthesis of Al-Ghazali’s and Bandura’s theories, emphasizing interactive and personalized content, with implications for digital literacy training for educators and content regulation